Preparation of Financial Statements for Village-Owned Enterprises (BUMDes) Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) - Haeruddin, Haeruddin; Ibrahim, Ibrahim; Jamali, Hisnol; HR, Agus Salim; Asriati, Asriati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Preparation of Financial Reports for Village-Owned Enterprises (Bumdes) Based on Financial Accounting Standards for Micro, Small Entities and Intermediate (SAK EMKM). This study aims to determine the presentation of financial statements based on the Financial Accounting Standards of the Minasa BUMDes Entity, Tamasaju Village, North Galesong District, Takalar Regency and compare it with the Financial Accounting Standards (SAK) of Micro, Small and Medium Entities (SAK EMKM). This study uses a qualitative descriptive research method, which is a research method that utilizes qualitative data and is described descriptively. The results showed that the preparation of the financial statements of the Minasa BUMDES in Tamasaju Village was not fully in accordance with SAK EMKM, this can be seen from the comparison of recognition, measurement, presentation and financial reporting. BUMDES financial reports are prepared very simply consisting of a profit and loss statement and a balance sheet, while the financial statements according to SAK EMKM consist of a profit and loss statement, balance sheet, statement of changes in equity and notes to financial statements (CALK).